Students' Islamic personality on ibadah: A structural modelling approach - Ismail, Nik Ahmad Hisham; Tekke, Mustafa; Othman, Nooraini; Abd Razak, Afareez (Elsevier, 2016)
The aim of this study was to examine the factorial structure of the Ummatic Personality Inventory. The sample of the study was a group of female students (n=287) a government school.Data was analysed using Confirmatory Factor Analysis and Structural Equation Modelling.